The effects of school entry laws on educational attainment and starting wages in an early tracking system - Martina Zweimüller (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2013)
Empirical evidence suggests that relative age, which is determined by date of birth and the school entry cutoff date, has a causal effect on track choice. Using a sample of male labor market entrants drawn from Austrian register data, I analyze whether the initial assignment to different school tracks has persistent effects on educational attainment and earnings in the first years of the career. I estimate the reduced-form effect of the school entry law on starting wages and find a wage penalty of 1.12.0 percent for students born in August (the youngest) compared to students born in September (the oldest). The analysis of educational attainment suggests that significant differences in the type of education exist. Younger students are more likely to pursue an apprenticeship and less likely to have higher education. After five years of labor market experience, the wage penalty amounts to 0.81.1 percent, suggesting a persistent (albeit decreasing) negative effect of the school entry rule on labor market outcomes in an early tracking system.
Keywords: I21; J24; J31; 330; School entry law; early tracking; educational attainment; earnings; labor market entrants